Endobronchial Inflammatory Myofibroblastic Tumor in a 3-Year-Old Child - Guanà, Riccardo; Carpino, Andrea; Miglietta, Marta; Zambaiti, Elisa; Cerrina, Alessia; Lonati, Luca; Guerrera, Francesco; Vallero, Stefano; Garofalo, Salvatore; Bardessono, Marco; Maletta, Francesca; Shilly, Steffi; Gennari, Fabrizio (European Journal of Pediatric Surgery Reports, 2023)
Inflammatory myofibroblastic tumor (IMT) is a mesenchymal tumor that can occur at any age. However, it is primarily seen in children, with the most common site being in the lung parenchyma, usually present with rare endobronchial lesions. This case reports the incidence in a 3-year-old girl diagnosed with pericardiac pneumonia treated with antibiotics with no clinical improvement. A chest computed tomography (CT) scan identified a 1.5-cm lesion in the left main bronchus. Bronchoscopy revealed complete obstruction of the left main stem bronchus. A left posterolateral thoracotomy was performed. Additionally, a left sleeve upper bronchial resection was conducted under fibroendoscopic control. Definitive histology confirmed IMT. After 2 years of endoscopic follow-up, there is no evidence of recurrence.
Keywords: myofibroblastic tumor; bronchoscopy; thoracotomy